Integrate senior leadership role with parenthood. Issue 8 (26th March 2019) - Tucker, Melanie V.
Abstract : A few years ago, I earned my doctorate, entered into my first vice presidency, and adopted my daughter — all within nine months of each other! Friends and family helped me balance full‐time work and dissertating. Mentors and professional resources helped me transition into a new role within a new campus community. However, I struggled to find guidance on how to best navigate senior leadership and motherhood.